1997
DOI: 10.1093/toxsci/38.1.101
|View full text |Cite
|
Sign up to set email alerts
|

The Ototoxicity of Trichloroethylene: Extrapolation and Relevance of High-Concentration, Short-Duration Animal Exposure Data

Abstract: Inhalation exposure to high concentrations of 1,1,2-trichloroethylene (TCE) has been shown to damage hearing in the mid-frequency range in the rat The present study directly evaluated the adequacy of high-concentration, short-term exposures to TCE for predicting the neurotoxicity produced by longer duration exposures. Adult male Long-Evans rats (n = 10-12 per group) were exposed to TCE via inhalation (whole body) in 1-m 3 stainless steel flow-through chambers for 6 hr/day, 5 days/week. The following exposures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The present work allows determination of these relationships. A 15-dB shift in an auditory threshold was nbsp;chosen as a change at one frequency that could be reliably detected in rats, and would be generally accepted as being clinically significant in humans (cf., Sataloff & Sataloff, 1993;Crofton & Zhao, 1997). The present rodent data demonstrate that a 15-dB hearing loss is associated with a T4 concentration of log 1.5934 or a 60% decrease in T4.…”
Section: Croftonsupporting
confidence: 52%
“…The present work allows determination of these relationships. A 15-dB shift in an auditory threshold was nbsp;chosen as a change at one frequency that could be reliably detected in rats, and would be generally accepted as being clinically significant in humans (cf., Sataloff & Sataloff, 1993;Crofton & Zhao, 1997). The present rodent data demonstrate that a 15-dB hearing loss is associated with a T4 concentration of log 1.5934 or a 60% decrease in T4.…”
Section: Croftonsupporting
confidence: 52%
“…These agents include chemical asphyxiants (e.g., Young et al 1987;Fechter et al 1988Fechter et al , 1997Fechter et al , 2002Fechter 1989;Rao and Fechter 2000) and solvents (e.g., Crofton 1994;Campo 1997;Johnson 1988;Crofton and Zhao 1997;Morata et al 1993Morata et al , 1994Morata et al , 1997a in addition to cisplatin (Gratton et al 1990) and aminoglycoside antibiotics (e.g., Bone and Ryan 1978;Brown et al 1980;Bhattacharyya and Dayal 1991). Prediction of additional agents that are able to increase the risk of severe NIHL is complicated by the tremendous variability in chemical structure and the diverse intentional uses of agents known to potentiate NIHL.…”
Section: Discussionmentioning
confidence: 99%
“…Organic solvents, known to be hazardous materials, can induce both central 2,3) and peripheral neurotoxicities 4) . It has been suggested that organic solvents can injure the sensory cells and peripheral nerve endings of the cochlea, and can affect the auditory pathways in the brain [5][6][7] . A retrocochlear influence can also be expected.…”
Section: Introductionmentioning
confidence: 99%